Factors that influenced turnover intention among employees in Nestle Manufacturing (M) Sdn.Bhd. / Mardiana Zakaria - Zakaria, Mardiana (Faculty of Business and Management, 2017)
This paper examines on employee turnover intention and the relationship with job satisfaction, organizational commitment, interpersonal relationship and job stress. This study highlights and defines basic concepts of job satisfaction, organizational commitment, interpersonal relationship and job stress and employee turnover intention. The studies have been done by the researcher to find the factors that influence turnover intention which is job satisfaction, organizational commitment, interpersonal relationship and job stress. The total sample size of the respondents was collected from 150 respondents, so then the data was processed by using multiple regression analysis software. The result shows that job satisfaction, organizational commitment, and interpersonal relationship have negative relationship toward turnover intention. Meanwhile job stress has positive relationship toward turnover intention. Besides that, the result also proved that interpersonal relationship is the most influence factor on turnover intention which 52% of R-Square value followed by job satisfaction 2.7% and organizational commitment 1.3%.